Measurement of gastric contraction activity in dogs by means of AC biosusceptometry - Moraes, R.; Cora, L. A.; Americo, M. F.; Oliveira, R. B.; Baffa, O.; Miranda, JRA (Iop Publishing Ltd, 2003)
The mechanical nature of gastric contraction activity (GCA) plays an important role in gastrointestinal motility. The aim of this study was to detect GCA in anaesthetized dogs, using simultaneously the techniques of AC biosusceptometry (ACB) and manometry, analysing the characteristics of frequency and amplitude (motility index) of GCA, modified by drugs such as prostigmine and N-butyl-scopolamine. The ACB method is based on a differential transformer of magnetic flux and the magnetic tracer works as a changeable external nucleus. This magnetic tracer causes a modification in the magnetic flux, which is detected by the coils. The results obtained from the ACB showed a performance comparable to the manometry in measuring the modifications in the frequency and amplitude of the GCA. We concluded that this ACB technique, non-invasive and free of ionizing radiation, is an option for evaluating GCA and can be employed in future clinical studies.
Keywords: susceptometry; manometry; biomagnetism; antral contraction